Kv1.1 channels mediate network excitability and feed-forward inhibition in local amygdala circuits - Samrat Thouta (Nature Portfolio, 2021)
Abstract Kv1.1 containing potassium channels play crucial roles towards dampening neuronal excitability. Mice lacking Kv1.1 subunits (Kcna1 −/− ) display recurrent spontaneous seizures and often exhibit sudden unexpected death. Seizures in Kcna1 −/− mice resemble those in well-characterized models of temporal lobe epilepsy known to involve limbic brain regions and spontaneous seizures result in enhanced cFos expression and neuronal death in the amygdala. Yet, the functional alterations leading to amygdala hyperexcitability have not been identified. In this study, we used Kcna1 −/− mice to examine the contributions of Kv1.1 subunits to excitability in neuronal subtypes from basolateral (BLA) and central lateral (CeL) amygdala known to exhibit distinct firing patterns. We also analyzed synaptic transmission properties in an amygdala local circuit predicted to be involved in epilepsy-related comorbidities. Our data implicate Kv1.1 subunits in controlling spontaneous excitatory synaptic activity in BLA pyramidal neurons. In the CeL, Kv1.1 loss enhances intrinsic excitability and impairs inhibitory synaptic transmission, notably resulting in dysfunction of feed-forward inhibition, a critical mechanism for controlling spike timing. Overall, we find inhibitory control of CeL interneurons is reduced in Kcna1 −/− mice suggesting that basal inhibitory network functioning is less able to prevent recurrent hyperexcitation related to seizures.